How do planets find their way? Laws of nature and the transformations of knowledge in the Scientific Revolution - Orozco-Echeverri, Sergio Hernán (The University of Edinburgh, 2020)
Laws of nature are perceived as playing a central role in modern science. This thesis investigates the introduction of laws of nature into natural philosophy in the seventeenth century, from which modern science arguably evolved. Previous work has indicated that René Descartes was responsible for single-handedly introducing a mathematical concept of laws into physics under the form of ‘laws of nature’. However, there is less agreement on the originality, causes and aftermath of this manoeuvre. This thesis is sensitive to the circumstance that the introduction of ‘laws of nature’ in the seventeenth century is a problem for us given our hindsight perspective of the origins of modern science, not an explicit concern of the actors; ‘laws of nature’ emerged as part of a network of problems and possibilities converging in Descartes’ reform of natural philosophy. Then, the appropriation of his laws was not an assessment of isolated statements on nature, but a process bounded by critical stances towards the Cartesian enterprise involving theological and social underpinnings. Accordingly, this thesis approaches ‘laws of nature’ as by-products of the changing boundaries between mechanics, mathematics and natural philosophy in the seventeenth century and interprets them as embedded within the circumstances and interactions among the practitioners of these disciplines in which these laws were introduced, criticised and appropriated. Based on this approach, this thesis tracks the background of Descartes’s project of reform of physics from the sixteenth-century fascination for machines that led to codifications of mechanics as a mixed-mathematical science, generating quantitative ways to design and fabricate physical (artificial) objects (Chapter 1). This approach was picked up by Galileo, who transformed it to include natural motion. In so doing, Galileo developed a mathematical approach to natural philosophy—a mathematical science of motion—which ultimately relied on the physical assumption of the motion of the Earth (Chapter 2). An alternative reorganization of mathematics and natural philosophy was put forward by the Lutheran theologian Kepler, wh o considered that the natural knowledge of the world may be founded a priori by deciphering the archetypes that God followed when creating the world. His archetypal cosmology provided a link between geometry and natural philosophy, involving mechanics (Chapter 3). However, Descartes moved in a different direction. Instead of connecting mathematics to natural philosophy, he tried to anchor both mathematics and natural philosophy on certainty, claiming that matter is but extension and that a few principles codified all possible interactions among parts of this geometrical matter. These principles were three ‘laws of nature’ erected as foundations of an a priori physics (Chapter 4). These ‘laws of nature’ received considerable attention in England. Informed by local traditions, English writers rejected the causal role attributed to laws but reworked their contents in laws of motion that were moved to mechanics and extended to astronomy, in line with the local practices of the ‘elliptical astronomy’ (Chapter 5). The relocation of ‘laws of nature’ from physics to mechanics was connected with English debates concerning the role of motion in geometry. These discussions drew different consequences for the connections between mathematics and nature (Chapter 6). In line with the English appropriation of Descartes, the young Newton assumed laws of motion as mathematical explanations in mechanics. When asked by Halley about orbital motion, his answer displayed characteristics of the English disciplinary setting. However, in connection with his historical studies, Newton realised that his laws of motion were capable of accounting for the true system of the world and then they were transformed into mathematical principles of natural philosophy, redrawing the contours of mathematics, natural philosophy and mechanics. The most important outcome of this reorganization—the law of gravitation—raised suspicions for going beyond the boundaries of established practices in the Continent (Chapter 7). The thesis concludes that ‘laws of nature’ did not emerge as a generic label to denominate findings in science. On the contrary, they appeared as concrete achievements with an operative function within Descartes’ reform of natural philosophy and consequently embedded within a network of assumptions, traditions and practices that were central to the appropriation of ‘laws of nature’. English natural philosophers and mathematicians reworked these ‘laws of nature’ within different disciplinary settings and put forward alternative ‘laws of motion’ in ways not previously noticed. The picture that emerges is not that of an amalgamation of previous meanings into a more complex one that was subsequently disseminated. Instead of a unified concept of ‘laws of nature’, Descartes’ project triggered reactions framed within local traditions and therefore it is hard to claim that at the end of the seventeenth century there was any agreement on the meaning of ‘laws of nature’ or even laws of motion beyond the narrow circles that shared disciplinary commitments and values. It was during the appropriation of Newton in the eighteenth century that his achievements and those honoured as his peers were labelled with a non- Newtonian concept of ‘laws of nature’, creating a foundational myth of the origins of modern science that reached up to the twentieth century.
Keywords: laws of nature; history of science; René Descartes; laws of motion; Royal Society of London; natural philosophy